The mediating role of self-efficacy in health literacy and chronic disease self-management in older individuals - Soylar, Pinar; Gornu, Besna (Bmc, 2026)
Background Chronic disease self-management (CDSM) is a vital component of healthy ageing, yet the interplay between its key determinants remains insufficiently understood. Health literacy and self-efficacy are widely recognized as important influences on older adults'ability to manage chronic conditions; however, the pathways linking these factors have received limited attention.This study examined the mediating role of general self-efficacy in the relationship between health literacy and CDSM among older adults with chronic diseases in T & uuml;rkiye. Methods A cross-sectional survey was conducted with 183 individuals aged 65 years and older. Participants completed the Health Literacy Scale, the General Self-Efficacy Scale, and the Chronic Disease Self-Management Scale. Data were analysed using descriptive statistics, Pearson correlation, and mediation analysis via Hayes' PROCESS macro with bootstrapping. Results The mean age of participants was 71.6 years (SD = 6.9), and 51.4% were female. Health literacy, self-efficacy, and CDSM were all positively correlated (p < .001). Mediation analysis demonstrated that self-efficacy fully mediated the relationship between health literacy and CDSM, accounting for 64.7% of the total effect. These findings highlight the role of self-efficacy as a psychological mechanism through which health literacy influences self-management behaviours. Conclusions Public health and health promotion initiatives targeting older adults should address both cognitive and psychosocial dimensions, aiming to strengthen self-efficacy alongside health literacy to support sustainable self-management and healthy ageing.
Keywords: Older Adults; Chronic Disease; Self-Management; Health Literacy; Self-Efficacy; Mediation; Nursing